A Characterization of Majority Rule for Hierarchies - McMorris, Fred R.; Powers, Robert C. (Journal of classification, 2008)
The majority rule has been a popular method for producing a consensus classification from several different classifications, when the classifications are all on the same set of objects and are structured as hierarchies. In this note, a new axiomatic characterization is proved for this consensus method on hierarchies.